Overview of growth differentiation factor 15 in metabolic syndrome. Issue 9 (29th March 2023) - Asrih, Mohamed; Wei, Shibo; Nguyen, Thanh T.; Yi, Hyon‐Seung; Ryu, Dongryeol; Gariani, Karim
Abstract: Growth and differentiation factor 15 (GDF15) is a member of the transforming growth factor‐β (TGF‐β) superfamily. GDF15 has been linked with several metabolic syndrome pathologies such as obesity and cardiovascular diseases. GDF15 is considered to be a metabolic regulator, although its precise mechanisms of action remain to be determined. Glial cell‐derived neurotrophic factor family receptor alpha‐like (GRAL), located in the hindbrain, has been identified as the receptor for GDF15 and signals through the coreceptor receptor tyrosine kinase (RET). Administration of GDF15 analogues in preclinical studies using various animal models has consistently been shown to induce weight loss through a reduction in food intake. GDF15, therefore, represents an attractive target to combat the current global obesity epidemic. In this article, we review current knowledge on GDF15 and its involvement in metabolic syndrome.